Aspek Citraan Pendengaran Dalam Kumpulan Cerpen Bulan Ziarah Kenangan Karya Sapta Arif Nur Wahyudin (Kajian Stilistika) - Setiawan, Agus; Manar Mustakim Kholil (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
This research aims to identify the use of sound imagery (auditory imagery) and its function in a collection of short stories by Sapta Arif Nur Wahyudin using a stylistic approach. Descriptive qualitative method is used to describe the findings of auditory imagery data in the form of words, phrases, and sentences. Documentation study is used as a data collection technique. The technique is carried out by reading the object of the short story collection, recording, and marking the data according to the research focus. Data were collected and checked again to avoid errors. Analysis of research data using flow model technique includes data classification, data reduction, data presentation, data interpretation and conclusion drawing. The results showed that five short stories entitled Bulan Ziarah Kenangan, Menerobos Lengkara, Apron Pink & Old Sewing Machine, Ritmis Classic Clock, and Lelaki Tua Bermata Seputih Susu contained auditory imagery that had different functions. The function is to create an atmosphere and describe the character's personality and emotions.